THE INFLUENCE OF INTEREST IN LEARNING AND MASTERING GRAMMAR ON THE STUDENTS' DESCRIPTIVE ENGLISH WRITING ABILITY Y AT PRIVATE HIGH SCHOOLS IN SOUTH TANGERANG - Adinda, Ismi; Anita Sari (Universitas PGRI Palembang, 2025)
This study examines the relationship between learning interest, grammar mastery, and descriptive writing skills among grade XI students at Private High Schools in South Tangerang. Learning interest plays a crucial role in student outcomes, as high interest fosters active engagement in learning, including in English language skills such as listening, speaking, reading, and writing. Descriptive writing is a key skill that many students struggle with, particularly when it comes to mastering grammar. The study focuses on how learning interest and grammar mastery influence students’ descriptive writing abilities, identifying obstacles that affect both factors. The research aims to provide insights into these influences and offer recommendations for improving writing skills. The findings are expected to benefit students, teachers, and future research by offering valuable information on grammar mastery and descriptive writing. Ultimately, the study seeks to enhance understanding of how learning interest and grammar knowledge affect descriptive writing skills in this context, offering practical guidance for educational development.